Evaluasi Sistem Akuntansi Dana Kas Kecil dalam Meningkatkan Akuntabilitas Pengeluaran Operasional Harian - Ayu Julsari (Expensive: Jurnal Akuntansi dan Keuangan, 2026)
PT ASSA Medan, applies the Imprest method in managing petty cash. However, several weaknesses remain evident, including reliance on manual recording, irregular transaction documentation, and delays in reconciliation, all of which may undermine accountability. This study aims to evaluate the petty cash accounting system of PT ASSA Medan by examining aspects of recording, documentation, and internal control, while also assessing its alignment with financial accountability principles. The research employs a qualitative descriptive approach through interviews, observations, and documentation analysis. The findings indicate that the implementation of the Imprest method is relatively effective in supporting daily operational efficiency, yet shortcomings persist in documentation consistency, timeliness of reconciliation, and segregation of duties. Although the system provides complete transaction evidence, dependence on manual recording increases the risk of errors. Based on these findings, the study recommends the digitalization of petty cash recording, reinforcement of standard operating procedures, and enhancement of monitoring mechanisms to strengthen accountability in cold chain-based distribution companies.